A synthesis of our current knowledge of philometrid nematodes, a group of increasingly important fish parasites - Moravec, Frantisek; de Buron, Isaure (Folia parasitologica, 2013)
Members of the Philometridae represent the most important group of dracunculoid nematodes parasitizing fishes. In his monograph treating the Dracunculoidea, Moravec (2006) reported a total of 11 genera and 105 species of philometrids parasitizing freshwater, brackish-water and marine fishes. However, during the last six years (2007-2012), an additional 42 new species of Philometridae have been described, representing a 40% increase of the number of nominal species. Most of these species (30) belong to Philometra Costa, 1845, mainly represented by parasites of marine fishes, a few others (8) to Philometroides Yamaguti, 1935, and a single one to each of the following genera: Caranginema Moravec, Montoya-Mendoza et Salgado-Maldonado, 2008, Dentiphilometra Moravec et Wang, 2002, Dentirumai Quiazon et Moravec, 2013* and Spirophilometra Parukhin, 1971. Moreover, three new genera, Afrophilometra Moravec, Charo-Karisa et Jirků, 2009, Caranginema and Dentirumai, were erected. Representatives of seven genera, Afrophilometra, Buckleyella Rasheed, 1963, Caranginema, Dentiphilometra, Dentirumai, Paraphilometroides Moravec et Shaharom-Harrison, 1989 and Rumai Travassos, 1960, were studied using scanning electron microscopy (SEM) for the first time. Thirteen known but poorly described philometrid species were redescribed and, in some species of Caranginema and Philometra, previously unknown conspecific males were discovered and described. The male surface ultrastructure studied by SEM provided new taxonomically important features for species distinction. Gene sequencing was used in several recent studies and advanced our understanding of phylogenetic interrelationships among representatives of seven genera (Afrophilometra, Alinema Rasheed, 1963, Caranginema, Nilonema Khalil, 1960, Philometra, Philometroides and Rumai) and of the extent of the biodiversity of philometrids. New data were obtained on the biology and pathogenicity of several species of Nilonema, Philometra, Philometroides and Rumai. The need to carry out surveys in order to find males and to use SEM and gene sequencing to identify philometrids is emphasized. Appropriate quantitative methods to determine the impact of philometrids in ovarian tissue on host fecundity are recommended. Further detailed studies on philometrids would be significant not only from the theoretical viewpoint, but also because of their practical implications. A list of philometrid nematode species by continents is provided.
Keywords: mořská voda; Dracunculoidea; Male; Fish Diseases; mužské pohlaví; sladká voda; Fresh Water; ryby; Spirurida Infections; Fishes; Animals; ženské pohlaví; Microscopy, Electron, Scanning; zvířata; nemoci ryb; infekce hlísticemi řádu Spirurida; Seawater; Female; mikroskopie elektronová rastrovací